Comparing the Accuracy of Three Pediatric Disaster Triage Strategies: A Simulation-Based Investigation. (8th January 2016) - Cicero, Mark X.; Overly, Frank; Brown, Linda; Yarzebski, Jorge; Walsh, Barbara; Shabanova, Veronika; Auerbach, Marc; Riera, Antonio; Adelgais, Kathleen; Meckler, Garth; Cone, David C.; Baum, Carl R.
Abstract: Background: It is unclear which pediatric disaster triage (PDT) strategy yields the best accuracy or best patient outcomes. Methods: We conducted a cross-sectional analysis on a sample of emergency medical services providers from a prospective cohort study comparing the accuracy and triage outcomes for 2 PDT strategies (Smart and JumpSTART) and clinical decision-making (CDM) with no algorithm. Participants were divided into cohorts by triage strategy. We presented 10-victim, multi-modal disaster simulations. A Delphi method determined patients' expected triage levels. We compared triage accuracy overall and for each triage level (RED/Immediate, YELLOW/Delayed, GREEN/Ambulatory, BLACK/Deceased). Results: There were 273 participants (71 JumpSTART, 122 Smart, and 81 CDM). There was no significant difference between Smart triage and CDM. When JumpSTART triage was used, there was greater accuracy than with either Smart ( P <0.001; OR [odds ratio]: 2.03; interquartile range [IQR]: 1.30, 3.17) or CDM ( P =0.02; OR: 1.76; IQR: 1.10, 2.82). JumpSTART outperformed Smart for RED patients ( P =0.05; OR: 1.48; IQR: 1.01, 2.17), and outperformed both Smart ( P <0.001; OR: 3.22; IQR: 1.78, 5.88) and CDM ( P <0.001; OR: 2.86; IQR: 1.53, 5.26) for YELLOW patients. Furthermore, JumpSTART outperformed CDM for BLACK patients ( P =0.01; OR: 5.55; IQR: 1.47, 20.0). Conclusion: Our simulation-based comparison suggested that JumpSTART triage outperforms both Smart and CDM. JumpSTART outperformed Smart for RED patients and CDM for BLACK patients. For YELLOW patients, JumpSTART yielded more accurate triage results than did Smart triage or CDM. ( Disaster Med Public Health Preparedness . 2016;10:253–260)